Identification of cobalt on a lattice site in diamond - Twitchen, D; Baker, M; Newton, M; Johnston, K (2000)
We report the finding of an electron-paramagnetic-resonance (EPR) center, labeled O4, which contains cobalt on a site in the diamond lattice. O4 is observed at low temperatures (<30 K) in high temperature and pressure synthetic diamonds grown with a cobalt containing metal-solvent catalyst after a high-temperature anneal at 1800°C. The center has S = 1/2, monoclinic I symmetry and a hyperfine splitting from a nucleus with I = 7/2. Analysis of the measured hyperfine interaction in terms of 3d5 gives the unpaired electronic wave function on the cobalt atom, and correctly predicts the measured g matrix. The wide linewidth of the EPR absorption suggests a small hyperfine interaction arising from a nearby nitrogen atom. Based on this evidence, a model for O4 is presented in terms of a CoN complex. ©2000 The American Physical Society.